Impact of the inclusion of chess as a gamiﬁcation tool for the development of useful personal skills for academic and work performance within the training processes. - Rodriguez, Miguel Angel
White starts the game using the Spanish opening with the purpose of strengthening the center of the board and developing the bishop to the corner of it, before this Black poses a Berlin defense threatening White's advance in the center with the knight; White begins the battle by proposing a queen's gambit seeking to consolidate his dominance in the center, Black reacts by proposing a Caro khan defense made up of a diagonal of pawns that constitutes the basis for a strong counterattack on the queenside... in short, these alternatives of game opening are part of a range of possibilities that chess players have to start the game. Possibilities that are not the result of chance but the result of theoretical developments that constitute the richness of since its inception. It is only a matter of remembering the king's annoyance with Sissa, son of the astronomer Daher, who according to Gude (1992), is the creator of chess. Annoyance caused when the ﬁrst wanted to reward him for creating the game and he asked for a grain of wheat for the ﬁrst square of the game, 2 for the second, 4 for the third and so on until completing the 64 squares of the board, the annoyance of the monarch it was because he thought it was a very simple and oﬀensive reward for the greatness of his kingdom, this did not occur until the court oﬃcials, continuing with the projection of grains and squares, found that ﬁnally Sissa should be given by projection geometric 18,446,744,073,709,551,615 grains of wheat. An amount that not even all the plots together could produce. This gives us the of the complexity of the game and is that contrary to what people without knowledge in the ma